A Round-Table Discussion - M. Sh. Khubutia; S. V. Gautier; M. A. Paltsev; A. G. Chuchalin; S. L. Dzemeshkevich; A. V. Chzhao; M. G. Minina; G. Sganga; S. U. Astanina; Ya. G. Moisyuk; M. M. Kaabak (Трансплантология (Москва))
A Round-Table Discussion.